2021
DOI: 10.1186/s42358-021-00216-1
|View full text |Cite
|
Sign up to set email alerts
|

Functioning in the fibromyalgia syndrome: validity and reliability of the WHODAS 2.0

Abstract: Background Fibromyalgia syndrome (FMS) is both a challenging and disabling condition. The International Association for the Study of Pain (IASP) classifies FMS as chronic primary pain, and it can negatively impact individuals’ functioning including social, psychological, physical and work-related factors. Notably, while guidelines recommend a biopsychosocial approach for managing chronic pain conditions, FMS assessment remains clinical. The WHODAS 2.0 is a unified scale to measure disability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…The above results should be interpreted in the light of a number of limitations. First, the FIQ-R does not provide a complete profile of the functioning of patients with FM; thus, future research should include specific indices of functioning such as the WHODAS 2.0 [85]. Second, the design of our study may make it difficult to differentiate between the effect of tDCS itself and the effect of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The above results should be interpreted in the light of a number of limitations. First, the FIQ-R does not provide a complete profile of the functioning of patients with FM; thus, future research should include specific indices of functioning such as the WHODAS 2.0 [85]. Second, the design of our study may make it difficult to differentiate between the effect of tDCS itself and the effect of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…for the test-retest reliability of the 36-item WHODAS 2.0 in individuals with FM were also obtained by Barreto et al 19 , although their study showed less stability in the domains of activity and participation. Other authors investigating the repeatability of measurements by means of the 36-item WHODAS 2.0 in different groups of patients with chronic diseases con rmed its very good test-retest reliability 36,37 .…”
Section: Discussionmentioning
confidence: 52%
“…The internal consistency of the 36-item WHODAS 2.0 was assessed using the Cronbach's Alpha coe cient, which was 0.95 for the total score, indicating high reliability of the scale. The Cronbach's Alpha coe cient for the 36-item WHODAS 2.0 in the Brazilian population was 0.91 19 . In other studies evaluating the psychometric properties of the 36-item WHODAS 2.0 in rheumatic or chronic diseases, authors also con rmed very good internal consistency of the tool 36,37 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation